PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V DI UPTD SDN LANDAK 1 TANAH MERAH - Aullia Dewi Safitri; Yunita Hariyani; Rendra Sakbana Kusuma (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
This study aims to determine the effect of the jigsaw type cooperative learning model on mathematics learning outcomes for class V at UPTD SDN Landak 1 Tanah Merah. This research uses a quantitative approach, the type of research is Pre-Experimental Designs One Group Pretest-Postest. The population in this study were all 15 students of class V UPTD SDN Landak 1 Tanah Merah. The t-test shows the correlation coefficient value of 0.796 with a sig value of 0.000 <0.05, it can be interpreted that the hypothesis is accepted. So in this study it can be concluded that there is an effect of the jigsaw type cooperative learning model on the learning outcomes of fifth graders.